- #1

Isaac0427

Gold Member

- 640

- 117

## Main Question or Discussion Point

We say that, for gravity, F=mg, where g≈-9.8 m/s

^{2}. Then, we have U=mgh. But, it seems like that equation would only work if g were positive 9.8 m/s^{2}. That is, because ##F=-\frac{dU}{dr}##, and ##\frac{dU}{dr}## is essentially ##\frac{dU}{dh}##, we should get F=-mg. So, for the two equations to work, it seems like the g in the first equation should have the opposite sign as the g from the second equation. But that seems like a really weird convention to have. So, if the convention is that g is positive then we should have F=-mg, and if g is negative we should have U=-mgh, right?